Spatial distribution of goat breeds bred in Benin - BEHINGAN, MILOGNON BORIS; MAMA, ADI; HOUNDONOUGBO, PASCAL VENANT; Koudande, O. D.; GLELE KAKAI, ROMIN LUCAS; CHRYSOSTOME, CHRISTOPHE ACHILLE A. MAHUSSI (My University, 2022)
Characterization of local goat breeds is an important step for the development of its breeding. This characterization cannot be done without knowing the size and the spatial distribution of the existing breeds. Thus, this work was carried out to study the spatial distribution of goat breeds bred in Benin. To achieve this, 498 breeders spread across the three climate zone of Benin were subjected to semi-structured individual interviews. The data collected were the socio-demographic characteristics of breeders, the number of breeds bred and the size of the herd per breed. Descriptive statistics, and the generalized linear model of Poisson family were used for data analysis. Results showed that breeders were mainly male (54.02%), married (88.15%) with a high rate of non-education (65.26%). The number of breeds bred by breeders in Guinean zone was 3 (West African Dwarf (WAD), Sahelian and Maradi goat) but 4 Soudanian and Soudano-Guinean zone (WAD, Sahelian, Maradi goat and Saanen). Despite the diversity of this breeds in the climate zone, only WAD breed was bred by more than 80% of breeders with a livestock size of 6133.
Keywords: Goat breeds; spatial diversity; Benin.